Differential gene expression in fronds and stolons of the siphonous macroalga, Caulerpa lentillifera. (11th November 2019) - Arimoto, Asuka; Nishitsuji, Koki; Narisoko, Haruhi; Shoguchi, Eiichi; Satoh, Noriyuki
Abstract: The green alga, Caulerpa lentillifera, is composed of a single cell with multiple nuclei, but it possesses structures analogous to leaves or fronds, stems or stolons, and roots or rhizoids. To understand molecular mechanisms involved in formation and function of these structures, we carried out RNA‐seq analysis of fronds and stolons (including rhizoids). Taking advantage of the decoded genome of C . lentillifera, the present RNA‐seq analysis addressed transcripts corresponding to 9, 311 genes identified in the genome. RNA‐seq data suggested that 8, 734 genes are expressed in sporophytes. Despite the siphonous body of the alga, differential gene expression was evident in the two structures. 1, 027 (11.8%) and 1, 129 (12.9%) genes were preferentially expressed in fronds and stolons, respectively, while the remaining 6, 578 (75.3%) genes were expressed at the same level in both. Most genes preferentially expressed in fronds are associated with photosynthesis and plant hormone pathways, including abscisic acid signaling. In contrast, those preferentially expressed in stolons are associated with translation and DNA replication. These results indicate that gene expression is regulated differently between fronds and stolons, which probably governs the function of each structure. Together with genomic information, the present transcriptomic data provide genic information about development and physiology of this unique, siphonous organism. Abstract : The green alga, Caulerpa lentillifera, is composed of a single cell with multiple nuclei. In spite of the siphonous body of the alga, differential gene expression was evident in the two structures.